BRICS and Covid-19- The Impact of COVID-19 on Educational Entrepreneurs in India with Special Reference to Central State: M.P. - Neerja Nigam; Manish Nigam (Journal of BRICS Studies)
After the historic disruption of the COVID-19 pandemic, no sector remained unaffected across the world, and similar to other critical sectors, the education sector too has been hit hard. Universities, colleges, schools, teachers, and the most vulnerable were the students who were deeply impacted. This calls for Governments, society, and specifically educational entrepreneurs, to re-think and put serious efforts into developing long-term strategies to meet the needs of education and ensure continued learning in unpredictable futures. In light of rising concerns, educational entrepreneurs have to redefine their way of working and have to include -online learning or e-learning as an integral part of their teaching process that too consistent basis.  This exploratory research paper proposes that educational entrepreneurs must adopt the latest technology and technological gadgets to sustain themselves in the market and grow. The inclusion of online learning or e-learning facilities along with the offline mode of teaching is a necessity in today’s dynamic environment.  However, in its adoption, numerous factors play a vital role and must be considered to motivate educational entrepreneurs. This research study has identified factors to be considered that not only have an impact on the adoption of technology but also support its consistent use.  Findings also reveal that apart from the identified factors, student’s and teachers’ digital readiness and motivation also play important roles in technological integration in the teaching process.